2014
DOI: 10.35790/eg.2.2.2014.5900
|View full text |Cite
|
Sign up to set email alerts
|

Uji Pengaruh Saliva Buatan Terhadap Kekuatan Tekan Semen Ionomer Kaca Tipe Ii Yang Direndam Dalam Minuman Isotonik

Abstract: The immersion of GIC type II in acid drink like isotonic drink could reduce the compressive strength (CS) of GIC type II. This is due to the matrix degradation process of  GIC in acid condition. But on the other hand, there is artificial saliva that can neutralize this condition. Purpose: Purpose of this study was to evaluate the effect of artificial saliva on compressive strength of GIC type II immersed in isotonic drink. Method: The GIC specimens of 6mm x 6mm x 12mm (length x width x depth) were immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
(1 reference statement)
1
4
0
6
Order By: Relevance
“…3 The results showed that the pH of each solution was 2.9 for river water, 7.5 for PDAM water, and 7 for sterile distilled water. This is in accordance with the theory of Fitriyana et al (2014) which states that materials exposed to an acidic pH will experience a higher decrease in mechanical properties, thus causing the value of the diametral tensile strength of the water settable GIC sample group immersed in river water to have the lowest value compared to with other sample groups. 14 Based on this research, it can be concluded that there is an effect of immersion in water settable GIC in river water and PDAM water on diametric tensile strength.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…3 The results showed that the pH of each solution was 2.9 for river water, 7.5 for PDAM water, and 7 for sterile distilled water. This is in accordance with the theory of Fitriyana et al (2014) which states that materials exposed to an acidic pH will experience a higher decrease in mechanical properties, thus causing the value of the diametral tensile strength of the water settable GIC sample group immersed in river water to have the lowest value compared to with other sample groups. 14 Based on this research, it can be concluded that there is an effect of immersion in water settable GIC in river water and PDAM water on diametric tensile strength.…”
Section: Discussionsupporting
confidence: 90%
“…In Fitriyana's (2014) study, it was stated that GIC suffered more morphological damage when it was in the oral cavity which had an acidic pH compared to those that only had contact with saliva. 14 The value of the diametrical tensile strength in the water settable GIC sample group immersed in PDAM water has a higher average value than the water settable GIC sample group immersed in river water and has a lower average value than the conventional GIC sample group immersed in aquadest which is equal to 8.42MPa. This is consistent with the research of Nadia et al, which states that PDAM water is not acidic, because filtration and coagulation has been carried out to neutralize the pH of the water.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations